2021
DOI: 10.1371/journal.ppat.1009321
|View full text |Cite
|
Sign up to set email alerts
|

Rab11a mediates cell-cell spread and reassortment of influenza A virus genomes via tunneling nanotubes

Abstract: Influenza A virus [IAV] genomes comprise eight negative strand RNAs packaged into virions in the form of viral ribonucleoproteins [vRNPs]. Rab11a plays a crucial role in the transport of vRNPs from the nucleus to the plasma membrane via microtubules, allowing assembly and virusproduction. Here, we identify a novel function for Rab11a in the inter-cellular transport of IAV vRNPs using tunneling nanotubes [TNTs]as molecular highways. TNTs are F-Actin rich tubules that link the cytoplasm of nearby cells. In IAV-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Although variation in the diversity generated through reassortment is apparent, visualization of viral antigen in infected tissues indicated that cellular co-infection is abundant at all sites examined. Cellular co-infection has previously been reported to be common in vivo 37 and is expected owing to the high potential for singular genomes to result in abortive infection 38 , 39 and the potential for direct cell-to-cell spread of viral genetic material 40 . Nevertheless, the juxtaposition of this result with a predominance of parental-type viruses in many samples is counter-intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Although variation in the diversity generated through reassortment is apparent, visualization of viral antigen in infected tissues indicated that cellular co-infection is abundant at all sites examined. Cellular co-infection has previously been reported to be common in vivo 37 and is expected owing to the high potential for singular genomes to result in abortive infection 38 , 39 and the potential for direct cell-to-cell spread of viral genetic material 40 . Nevertheless, the juxtaposition of this result with a predominance of parental-type viruses in many samples is counter-intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Although variation in the diversity generated through reassortment is apparent, visualization of viral antigen in infected tissues indicated that cellular co-infection is abundant at all sites examined. Cellular co-infection has previously been reported to be common in vivo 34 and is expected owing to the high potential for singular genomes to result in abortive infection 35,36 and the potential for direct cell-to-cell spread of viral genetic material 37 . Nevertheless, the juxtaposition of this result with a predominance of parental-type viruses in many samples is counter-intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, it was found for the first time that a virus (HIV-1) can be transmitted through TNT [ 5 ]. Subsequent studies found that viruses such as orthomyxoviruses (e.g., influenza A virus, IAV) [ 6 ] and alphaherpesvirus (e.g., pseudorabies virus, PRV) [ 7 ] can spread through TNTs. The formation of TNT is a new mode of virus transmission, which facilitates the virus to spread to non-adjacent cells.…”
Section: Introductionmentioning
confidence: 99%